Development of system for displacement measurement of a cantilever beam with strain gauge sensor - Dejan Shishkovski; Zlatko Petreski; Goce Tasevski (Mechanical Engineering – Scientific Journal, 2015)
In this paper, strain gauge based experimental system for displacement measurement of a cantilever beam was developed. The system comprises strain gauge sensors, signal conditioning module and data acquisition unit. Two strain gauges installed at the beam surface are connected in Wheatstone half-bridge configuration. Signal conditioning process is described in details along with the procedure for signal processing. Eventually, experimental investigations were conducted to verify the analytical gained results and certain conclusions were drawn.